Khūm̄ư patibat ngān kīeokap thīdin sāthārana prayōt thī rātchaphatsadu læ kānhai khr̄ưangmāi t̨ōpth̄æn phūchūail̄ưa rātchakān phonlar̄ưan (Samnak B̨ōrihān Kānpokkhr̨ōng Th̨ōngthī, Krom Kānpokkhr̨ōng, 1999)
Land usage under the Department of Local Administration of Thailand.